1991
DOI: 10.1091/mbc.2.3.181
|View full text |Cite
|
Sign up to set email alerts
|

Association of the crosslinked IgE receptor with the membrane skeleton is independent of the known signaling mechanisms in rat basophilic leukemia cells.

Abstract: Crosslinking of the IgE receptor on the surface of rat basophilic leukemia (RBL) cells by multivalent antigen induces an association of these receptors with the detergent-insoluble membrane skeleton. Detergent insolubility of the receptor can also be induced on purified plasma membranes isolated from RBL cells by the use of either IgE oligomers or IgE monomers plus multivalent antigen. The critical event in initiating this interaction between the receptor and the membrane skeleton is crosslinking of the recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…USA 89 (1992) the P815 cells synthesize endogenously (16). That the aggregated receptors were efficiently insolubilized in these transfectants is consistent with other data that show that the aggregation that leads to insolubilization is independent of, and might even suppress, cellular activation (5,19,28). Our data that aggregated receptors on COS cells are efficiently insolubilized are also confirmatory, since there is no evidence that these cells are activated by transfected FcERI (L. Miller, C. Fewtrell, G.A., C. Jelsema, and H.M., unpublished data).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…USA 89 (1992) the P815 cells synthesize endogenously (16). That the aggregated receptors were efficiently insolubilized in these transfectants is consistent with other data that show that the aggregation that leads to insolubilization is independent of, and might even suppress, cellular activation (5,19,28). Our data that aggregated receptors on COS cells are efficiently insolubilized are also confirmatory, since there is no evidence that these cells are activated by transfected FcERI (L. Miller, C. Fewtrell, G.A., C. Jelsema, and H.M., unpublished data).…”
Section: Discussionsupporting
confidence: 88%
“…Insolubilization shows a lesser dependence on temperature than does internalization (5,19,28) and is relatively insensitive to cytochalasins (20). Furthermore, in the cells we examined, if anything, insolubilization was more prominent in the COS cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A similar set of intracellular signal transducing mediators is found in other cells manifesting ligand-induced exocytosis of intracellular granules, in particular, mast cells and basophils, and, in this exocytotic reaction, a transient increase in intracellular Ca2+ is observed (Penner, 1988;Koopman and Jackson, 1990;Benhamou et al, 1990). It is of interest that, in these cells, the signal pathways initiated by ligand-induced receptor aggregation with consequent activation of tyrosine kinase (TK) activity and those activated by Ca2+ influx intersect at effector levels at considerable remove "downstream" from the ligand-induced stimuli (Penner, 1988;Benhamou et al, 1990;Apgar, 1991). Roldan andHarrison (1989, 1990a,b) have reported that Ca2+ influx induced by the ionophore A23187 can trigger polyphosphoinositide breakdown in sperm from ram, boar, mouse, human, and guinea pig and that this reaction occurs under conditions in which acrosomal exocytosis is effected by ionophore treatment.…”
Section: Examination Of Figuresmentioning
confidence: 99%